PERPUSTAKAAN DATA : SEBUAH PENGAMAT TERHADAP UNIVERSITY OF TORONTO MAP AND DATA LIBRARY - Thoriq Tri Prabowo (Perpustakaan Nasional RI, 2016)
Data libraries have been widely known in Europe and America. The fact that these libraries have been optimized for upporting research makes it significant for Indonesia to initiate the development data libraries. However, Indonesian language literature on this specific type of library is still very limited. Although some of data library aspects have been considerably implemented, the author has not found any data library exist in Indonesia. Therefore, this paper is aimed at defining a representative data library by looking at the University of Toronto Map and Digital Library, as one of data libraries, and observing its facilities. The author will attempt to make a basic observation and description in regard. It is expected that the results will be useful as a reference for developing data libraries in Indonesia.